OXIDATIVE MODIFICATION OF PROTEINS IN RAT SERUM UNDER EXPERIMENTAL OSTEOARTHRITIS AND JOINT ADMINISTRATION OF CHONDROPROTECTOR AND MULTIPROBIOTIC - KOROTKYI, O.; KOT, L.; DVORSHCHENKO, K.; OSTAPCHENKO, L. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
One of the actual problems of modern medicine is joint disease. Among them, osteoarthritis occupies an important place. The formation of osteoarthritis is accompanied by the development of inflammation, which leads to damage to all structures of the joint. An important role in inflammatory processes is played by the intensification of free radical processes. As the disease develops, the joints lose their mobility, which leads to a decrease in the quality of life of patients and the development of disability. In this regard, it is important to search for drugs that have regenerative, anti-inflammatory and antiradical properties. The aim of our study was to investigate the combined effect of chondroitin sulfate and multiprobiotic on the content of oxidative protein modification products and the level of sulfhydryl groups in rat blood serum under conditions of monoiodoacetate-induced osteoarthritis. The study included participation of white male non-linear rats (weighing 180–240 g) adherence to the general ethical principles of animal experiments. An experimental osteoarthritis model was created by introducing 1 mg of sodium monoiodoacetate into the knee ligament. Chondroitin sulfate and multiprobiotic were used as therapeutic agents. The content of products of oxidative modification of proteins was determined by the level of carbonyl derivatives, which are manifested in the reaction with 2,4-dinitrophenylhydrazine. The level of total, protein-bound and non-protein sulfhydryl groups was measured by the Elman method. It was found that under conditions of monoiodoacetate-induced osteoarthritis in the blood serum of rats, the content of products of oxidative modification of proteins increases. The level of neutral aldehyde products (E max = 356 nm) is increased by 2.5 times and neutral ketone products (E max = 370 nm), respectively, by 2,1 times compared to the control. Under the same experimental conditions in the blood serum, the amount of basic aldehyde products (E max = 430 nm) increases by 1.9 times, while the content of the main ketone products (E max = 530 nm) increases by 1,7 times compared to the control groups. In experimental osteoarthritis in the blood serum, the content of sulfhydryl groups decreases: non-protein SH-groups – 1,5 times, protein and general SH-groups – 1,7 times relative to the control. This indicates disturbance of the oxidative-antioxidant balance and the development of oxidative stress in the organism during experimental osteoarthritis. It was shown that the combined administration of chondroitin sulfate and multiprobiotics in animals with experimental osteoarthritis partially restored the above parameters.
Keywords: experimental osteoarthritis, chondroitin sulfate, multiprobiotic, oxidative modification of proteins, blood serum